Evaluation of post-earthquake fire capacity of a reinforced concrete one bay plane frame under ISO fire exposure - Vitorino, Hugo (2019)
Post-earthquake fires may appear after a large earthquake and its effects on urban areas can be even worse that the effects of the earthquake itself. The aim of the present work is to define a methodology to evaluate the consequences of the damage introduced by the seismic events on the fire resistance of reinforced concrete frames. It was performed several numerical analyses in reinforce concrete frames using the program SAFIR, considering the thermal and mechanical analysis of the structure. The variables in the analysis were the type of damage in the frames and the number of fire frontiers in the columns. The thermal analysis was performed using the standard fire curve ISO 834. The results show that the damage imposed by earthquake on reinforced concrete frames reduces the fire resistance of the frames. The time until collapse of the frames exposed to fire where was considered the most severe damage was about 2 h lower when compared to the frames without damage exposed to fire.